Pyogenic granuloma arising within capillary malformations in children: A case report and literature review - Alessandra Rancan; Alessandro Boscarelli; Daniela Codrich; Irene Berti; Edoardo Guida; Jürgen Schleef (PAGEPress Publications, 2021)
Pyogenic granuloma (PG) is an acquired benign vascular hyperplasia. Even though PG is not so rare, its etiology is still unclear. Assuredly, an association between vascular anomalies and PG is an extremely rare finding, and a proper management of these cases is not well standardized to date. Herein, we report our experience with a giant PG arising spontaneously within a port-wine stain of the thorax. Previous cases reported in the pediatric literature and strategies of treatment are also discussed.